Sensitivity of Larva Spodoptera litura Against the Density of Spores of Fungi Metarhizium anisopliae on the Onion Plant Red (Allium cepa) in the Laboratory - Brijayanti Halawa; Azwana Azwana; Ellen L. Panggabean (Budapest International Research and Critics University, 2019)
Sensitivity of Larva Spodoptera litura Against the Density of Spores of Metarhizium anisopliae Fungi On the Red Onion Plant